Perbandingan Hasil Belajar Materi Sistem Pencernaan Makanan pada Model Pembelajaran Reciprocal Teaching yang Menggunakan Game Smart Case Dengan yang Tidak Menggunakan Game Smart Case Peserta Didik SMA Negeri 1 Barru - Andi Irna Lestari Husni; Mushawwir Taiyeb; Fatmah Hiola (Universitas Sebelas Maret, 2018)
This study aims to determine the comparison learning outcomes digestive system material in reciprocal teaching learning model used game smart case with not used game smart case students SMA Negeri 1 Barru. The sample in this research is the students of class XI MIA 4 as experiment class 1 and class XI MIA 7 as experiment class 2 which amounts to 70 students obtained by using simple purposive sampling technique. This research uses quasi experimental research design pretest-posttest non equivalen comparison group design. The cognitive learning outcomes were measured using a multiple choice test of 30 numbers and a description test of 5 numbers on the dietary material of the digestive system. The data obtained were analyzed by descriptive statistic and inferential statistic using paired sample anacova test with significance level 0,05. The result of t test statistic for students' cognitive learning result is 0,004 means Ho is rejected and H1 accepted so that it can be concluded that there is a comparison learning outcomes digestive system material in reciprocal teaching learning model used game smart case with not used game smart case students.